2003
DOI: 10.1021/jf030137j
|View full text |Cite
|
Sign up to set email alerts
|

Apple and Pear Peel and Pulp and Their Influence on Plasma Lipids and Antioxidant Potentials in Rats Fed Cholesterol-Containing Diets

Abstract: The aim of this study was to assess the bioactive compounds of apple and pear peel and pulp in vitro and their influence on plasma lipids and antioxidant potentials in vivo. The antioxidant potentials measured by 1,1-diphenyl-2-picrylhydrazyl (DPPH), beta-carotene bleaching (beta-carotene), and nitric oxide inhibition radical scavenging (NO) tests in apple peel and pulp were significantly higher than in pear peel and pulp, respectively. The ethanol extract of apple peels showed the strongest inhibition of lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
119
4
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 30 publications
16
119
4
7
Order By: Relevance
“…The antioxidant activity of these peels was also much greater when compared to the flesh (WOLFE; LIU, 2003). This work is supported by Leontowicz et al (2003), who found that rats consuming apple peels showed greater inhibition of lipid peroxidation than rats fed apple flesh.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…The antioxidant activity of these peels was also much greater when compared to the flesh (WOLFE; LIU, 2003). This work is supported by Leontowicz et al (2003), who found that rats consuming apple peels showed greater inhibition of lipid peroxidation than rats fed apple flesh.…”
supporting
confidence: 55%
“…This result is in accordance with Aprikian et al (2002), who found that when cholesterol-fed rats were supplemented with apples, there was a significant drop in plasma cholesterol and an increase in high-density lipoproteins (HDL). More studies investigated these parameters using apples, pears and peaches, with apples having the greatest effect (BOBEK; OZDÍN; HROMADOVÁ, 1998;LEONTOWICZ et al, 2003). Apples contained more phenolic compounds, suggesting that perhaps the phenolics in apples contribute to this effect ( LEONTOWICZ et al, 2002).…”
Section: Hdl-cmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature during the sample storage (30°C) had a significant influence, resulting in a higher degradation of all phenolics compounds analysed, colour and antioxidant activity. A high intake of fruits and their products is generally acknowledged to promote good health and lower the risk of diseases, such as coronary heart disease and cancer, which implicate the oxidative stress as part of their pathogenesis or progression.Oxygen free radicals and lipid peroxidation may be involved in pathological conditions, such as arteriosclerosis, cancer, and chronic inflammation (Leontowicz et al 2003;Lotito & Frei 2004). …”
mentioning
confidence: 99%
“…Oxygen free radicals and lipid peroxidation may be involved in pathological conditions, such as arteriosclerosis, cancer, and chronic inflammation (Leontowicz et al 2003;Lotito & Frei 2004).…”
mentioning
confidence: 99%